Public Value Creation in Local Government Context: A Bibliometric Analysis - Widiono, Genut Wahyu; Fathurrahman, Reza; Wijaksono, Jagad (Journal of Local Government Issues, 2024)
The purpose of this study is to identify the development of the public value creation’s concept in the context of local government in the last twenty years (2002 – 2022). The 177 scientific publications in the form of articles and conference papers that were selected from the Scopus Database were further analyzed using bibliometric analysis, which combined performance analysis and science mapping techniques. The analysis results show an increase in the number of publications dominated by western countries which can be categorized into five research clusters: e-government, smart city, public governance, co-creation, and public management. The researcher recommends fifteen research topics that can be explored further in future research.